Determinantes do desempenho dos alunos das Instituições de Ensino Superior Brasileiras no ENADE 2013 - Araújo, Fátima Helena Ramos de (2017)
The present work investigates the determinants of the academic performance of students of Higher Education Institutions(IES)in Brazil.Todoso,weusethemic rodata from the National Student Performance Examination(ENADE)fortheyear2013.Based on the generalnotes obtained by students and the iranswerstothesocioeconomicquestionnaire,econometric models of linear and quantileregressionwerebuilt.There sult sindicate both socioeconomic factors such asage,gender,race,and familyincome,as wellascharacteristicsofthestudent’sownIES, such as there gionwhereitisinsertedandwhetheritispublicorprivate,canpartiallyexplaina variation of studentscores